(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This scientific article comprehensively analyzes the importance of Islamic finance’s main financial instruments corresponding to Islamic finance - sukuk - in the modern global financial system. The study carefully studied the international experience gained in the process of using these instruments not only in Muslim countries, but also in the global financial markets.